Determination of the Effects of Different Irrigation Strategies on Leaf Osmotic Potential and K and Ca Ion Concentrations in Red Pepper with Furrow and Drip Irrigation Methods - Akhoundejad, Yelderem; Sezen, Semih Metin; Dasgan, Hayriye Yildiz (Kahramanmaras Sutcu Imam Univ Rektorlugu, 2024)
A study was managed to identify the water stress effect on marketable yield, osmatic potential, and potassium (K) and calcium (Ca) ions for drip and furrow irrigated processing red pepper in the 2010 and 2011 growing seasons in Tarsus, Turkey. The treatments for drip irrigation; comprise full irrigation (DFI1.0), deficit irrigation DDI0.75, DPRD0.5, DFPRD0.5, and DDI0.5; for furrow irrigation; full irrigation (FFI1.0), fix alternative furrow (FAF0.5) and PRD furrow (FPRD0.5). FAF0.5 and FPRD0.5 received 50 % of the water applied to FFI1.0. In FAF0.5 the same furrows were irrigated while in FPRD0.5 irrigated alternately. Irrigation methods and irrigation levels had a remarkable effect on the total yield of red pepper in both experimental years. Drip irrigation treatments manufactured higher red pepper yields than the furrow irrigation treatments. The maximum yield in the drip irrigation system was acquired from the DFI1.0 treatment followed by DDI0.75, DDI0.5, and DFPRD0.5 treatments. Though DPRD0.5, DFPRD0.5, and DDI0.5 applied the same amount of water, DPRD0.5 resulted in a higher yield. In furrow treatments, FFI1.0 resulted in the highest yield followed by FPRD0.5 and FAF0.5. Water use efficiency (WUE) diminished with increasing the water amount for drip and furrow irrigation methods. While lower osmotic potential values were measured in full irrigation treatments in furrow and drip irrigation plots, higher osmotic potential values were determined in treatments where water stress was determined in both years. In both drip and furrow irrigation, the lowest Ca (%) values were obtained in full irrigation, while the highest Ca values were obtained in limited irrigation with water stress in the 2010 and 2011 years. K ion values were generally similar in the first and fourth pepper harvests in drip and furrow irrigation.
Keywords: Pepper; Furrow; Drip irrigation; Osmotic potential; Partial root drying